Analysis of various electron blocking layers to improve efficiency in green light-emitting diodes. Issue 11 (1st August 2020) - Usman, Muhammad; Anwar, Abdur-Rehman; Saba, Kiran; Munsif, Munaza
Abstract: Efficiency of GaN-based green light-emitting diodes with various electron blocking layers has been studied numerically. By employing conventional AlGaN, graded AlGaN, quaternary AlGaInN and ternary AlInN electron blocking layers, performance of each device has been evaluated. The device characteristics presented include carrier transport, radiative recombination rate, electrostatic field, emission spectra and efficiency.